The first target experiments on the national ignition facility - Landen, O; Glenzer, S; Froula, D; Dewald, E; Suter, L; Schneider, M; Hinkel, D; Fernandez, J; Kline, J; Goldman, SR; Braun, D; Celliers, P; et al. (2007)
A first set of shock timing, laser-plasma interaction, hohlraum energetics and hydrodynamic experiments have been performed using the first 4 beams of the National Ignition Facility (NIF), in support of indirect drive Inertial Confinement Fusion (ICF) and High Energy Density Physics (HEDP). In parallel, a robust set of optical and X-ray spectrometers, interferometer, calorimeters and imagers have been activated. The experiments have been undertaken with laser powers and energies of up to 8 TW and 17 kJ in flattop and shaped 1-9 ns pulses focused with various beam smoothing options. The experiments have demonstrated excellent agreement between measured and predicted laser-target coupling in foils and hohlraums, even when extended to a longer pulse regime unattainable at previous laser facilities, validated the predicted effects of beam smoothing oil intense laser beam propagation in long scale-length plasmas and begun to test 3D codes by extending the study of laser driven hydrodynamic jets to 3D geometries.